Safety and Efficacy of Second Ahmed Valve Implant in Refractory Glaucoma - Chiara Posarelli (Journal of Clinical Medicine, 2020)
Background: Refractory glaucoma still represents a challenge for ophthalmologists to manage intraocular pressure. The present study aimed to evaluate long term efficacy and safety of a second Ahmed valve implantation after the failure of a first implant in patients with refractory glaucoma and elevated intraocular pressure (IOP). Methods: Retrospective, multicenter non-comparative case series. Twenty-eight patients were retrospectively recruited between January 2011 and December 2017. Demographic data, glaucoma type, visual acuity, intraocular pressure, medical therapy, and complications were registered. Three criteria of success were established: Type 1 surgical success: IOP ≤ 15 mmHg and a reduction of IOP ≥ 40% from baseline; Type 2 surgical success: IOP ≤ 18 mmHg and a reduction of IOP ≥ 30% from baseline; and Type 3 surgical success: IOP ≤ 21 mmHg and a reduction of IOP ≥ 20% from baseline. Surgical failure has been established as IOP less than 5 mmHg or over 21 mmHg and less than a 20% reduction of IOP from baseline despite medications in two consecutive visits, light perception loss referable to glaucoma, and the necessity for further glaucoma surgery. Failure was observed in six (21%) patients. (3) Results: Mean IOP and mean glaucoma medication number significantly reduced from baseline after the second implantation, and the surgical success rate at 72 months ranged from 10% to 78% based on the different criteria of success. Failure was observed in six (21%) patients. Conclusions: This study confirmed the safety and efficacy of a second Ahmed valve implantation in patients with refractory glaucoma and elevated IOP at baseline.